Meaning Making Process and Recovery Journeys Explored Through Songwriting in Early Neurorehabilitation: Exploring the Perspectives of Participants of Their Self-Composed Songs Through the Interpretative Phenomenological Analysis - Baker, Felicity A.; Tamplin, Jeanette; Rickard, Nikki; New, Peter; Ponsford, Jennie; Roddy, Chantal; Lee, Young-Eun C. (Frontiers in Psychology, 2018)
Objectives: This pilot study examined how fifteen participants in early rehabilitation described their self-composed songs six- to twelve-months following participation in a 6-week identity-focused songwriting program. Specific focus was given to the process of meaning making and identity reconstruction in the participants' self-composed songs. Methods: Data were collected through individual semi-structured interviews (n = 15) and analysed using interpretative phenomenological analysis. Findings were developed idiographically as super-ordinate themes unique to each participant, then analysed across cases to identify recurrent themes and subthemes. Results: Participants described the songwriting process as taking them through one of four distinct recovery journeys described by individuals following acquired neurodisability who underwent a focused therapeutic songwriting program. These included 1) re-conceptualising values and shifting perspectives about self (my body is broken but my mind has been set free); 2) recognising acquired inner resources to negotiate discrepancies in self (hope is there); 3) confirming existing values and identifying resources and coping strategies (I have what I need to move forward); 4) confirming previously held values and ongoing process of negotiating discrepancies in self (I don't yet have the answers). Conclusions: The current study provides insight into the nature and process of meaning making and recovery journeys perceived by individuals with neurodisability. Our findings suggest that songwriting could be a therapeutic tool to facilitate identity reconstruction in neurorehabilitation.